The antibacterial activities of Peppermint oil, Mustard oil and Clove oil on Klebsiella pneumonia, Acinetobacter baumannii, and Pseudomonas taetrolens - Meem, Umara (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.